Respuestas
Respuesta dada por:
4
En la primera ecuación
![13x - 9y = 50 \\ 13x - 50 = 9y 13x - 9y = 50 \\ 13x - 50 = 9y](https://tex.z-dn.net/?f=13x+-+9y+%3D+50+%5C%5C+13x+-+50+%3D+9y)
Reemplazamos en la segunda ecuación
![10x + 13x - 50 = 26 \\ 23x = 76 \\ x = \frac{76}{23} = 3.3 10x + 13x - 50 = 26 \\ 23x = 76 \\ x = \frac{76}{23} = 3.3](https://tex.z-dn.net/?f=10x+%2B+13x+-+50+%3D+26+%5C%5C+23x+%3D+76+%5C%5C+x+%3D++%5Cfrac%7B76%7D%7B23%7D++%3D+3.3)
Reemplazamos en la segunda ecuación
dannyrivera300pcjrep:
y si fuera por igualacion como seria
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años